BIBLIOMETRIC ANALYSIS: DEVELOPMENT AND DYNAMICS OF PUBLIC SERVICE RESEARCH FOR PEOPLE WITH DISABILITIES - Artanti, Cheryl Amelia; Permatasari, Indah; Imania, Katriza; Thamrin, M. Husni (Program Studi Sosiologi Universitas Malikussaleh, 2024)
This study aims to present a bibliometric analysis of the research development on public services for disabilities from 2015 to 2023. The study utilizes data from the Scopus database using the keyword